Using mixed methods : frameworks for an integrated methodology - Plowright, David (London : SAGE, 2011)
Using Mixed Methods" offers an innovative approach to social and educational research. The author sets out the case for research from a holistic perspective, integrating different methods, different data and overall research strategies. This book shows how to use an integrated methodology that meets the needs of the postgraduate researcher who wants to challenge the traditional paradigmatic view of research. The author explores: the FraIM and its application to social and educational research; the contexts of research; different methods of data collection; and types of data and their natural integration within the research process. This book is for final year undergraduate and postgraduate students on social science and education courses.
Includes bibliographical references and index.
oif 13/06/14
Loan
Keywords: Social sciences -- Research -- Methodology; Research -- Methods. Research design; Research methodology. &#x000A